Cytokines and other important inflammatory mediators in gestation and bacterial intraamniotic infections - Splíchal, I; Trebichavský, I (Folia microbiologica, 2001)
Intraamniotic infections caused by viruses, bacteria or mycoplasmas are frequently followed by damage of fetus or increased perinatal morbidity and mortality. Cytokines are key substances regulating a number of biological processes including reproductive and inflammatory processes. An association between intraamniotic infections, rising concentrations of inflammatory cytokines in amniotic fluid and preterm labor is suggested. A great effort is made to find reliable markers typical for intraamniotic infections with high predictive value that make possible prompt identification of patients with intraamniotic infection. This review concerns inflammatory mediators, especially IL-1, IL-6, IL-8, TNF-alpha, and other important biologically active substances as prostaglandins and NO metabolites and their roles in intraamniotic infections. Finally, we discuss their relevance for diagnosis of intraamniotic infections.
Keywords: plodová voda; Bacterial Infections; infekční komplikace v těhotenství; gestační stáří; mediátory zánětu; cytokiny; Gestational Age; Pregnancy; těhotenství; amnion; bakteriální infekce; Amniotic Fluid; lidé; ženské pohlaví; Humans; Amnion; Pregnancy Complications, Infectious; Cytokines; Inflammation Mediators; Female